Predation of Sumichrast’s vesper rat Nyctomys sumichrasti by the lizard Basiliscus plumifrons - Alvarado, Randy; Mora, José Manuel (Therya Notes, 2023)
There are 33 Cricetidae species in Costa Rica, including Sumichrast's vesper rat, Nyctomys sumichrasti. It is relatively uncommon but potentially locally common to abundant. In Costa Rica, it primarily inhabits the canopy and is rarely seen due to its nocturnal and arboreal habits. In México, it has been observed both in treetops and on the ground amidst dense vegetation and trees. During a tour at Selva Verde Lodge in northern Costa Rica, we observed a predation event. We took pictures of it from about 5 m avoiding disturb the predator. We identified the predator on site, and later we confirmed the prey identification reviewing our pictures and comparing them with other pictures and field guides and taxonomic keys. On March 19, 2023 at 17:28 hr we observed an adult female green basilisk (Basiliscus plumifrons) preying and consuming a Sumichrast's vesper rat. The basilisk chased the rat across the floor, grabbed it with its jaws, killed it and then swallow it. The whole process took about 40 min. Nyctomys sumichrasti visits buildings at Selva Verde where basilisks are always present. These basilisks are diurnal while N. sumichrasti is nocturnal, but they can coincide in activity and location. Recently, a female basilisk hunted a night lizard, and weeks earlier, a male of the same species consumed a young green iguana at the same area.